Strengthening Students' Learning Independence through Self-Regulated Learning in Islamic Boarding School Environments - M. Makhrus Ali; Firmansyah Firmansyah; Hoiri Hoiri; Soni Putra; Erdiyansyah Erdiyansyah; Muhammad Yusuf (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
This study aims to analyze the implementation of Self-Regulated Learning in strengthening the learning independence of students at Darul Khoir Islamic Boarding School. The study used a qualitative approach with a case study type. Data collection techniques were carried out through observation, interviews, and documentation of the boarding school caretakers, ustadz, administrators, and students. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that first, the implementation of Self-Regulated Learning is carried out through the habituation of students in preparing study schedules, determining academic and memorization targets, managing study time, and conducting independent learning evaluations. Second, supporting factors for strengthening learning independence include a disciplined boarding school environment, support from ustadz, religious culture, and social interaction between students, while obstacles found include dependence of some students on the ustadz's direction, low time management skills, and the influence of social media on learning focus. Third, the implementation of Self-Regulated Learning has positive implications for the academic development and character of students, such as increased learning motivation, critical thinking skills, discipline, responsibility, and self-confidence. This research shows that Self-Regulated Learning is an effective approach in building independent learning among students in Islamic boarding schools.